Формування обсягів виробництва послуг автосервісу - Гарачук, О. В.; Кузьмін, В. С.; Акімова, В. П. (НТУ "ХПІ", 2013)
На основі теоретичних досліджень розроблена модель формування обсягів виробництва послуг на підприємстві автосервісу. Модель містить три складові функції: функції негативного і позитивного впливу на збільшення обсягів послуг та функцію планового розвитку обсягів послуг. Розроблено рекомендації по використанню моделі, представлена загальна методика формування обсягів послуг. Модель базується на забезпеченні сталого розвитку виробництва.

On the basis of theoretical researches the model of formation of volumes of manufacture of services at the car-care centre enterprise is developed. The model contains three compound functions: functions of negative and positive influence on increase in volumes of services and function of planned development of volumes of services. Recommendations about model use are developed, the general technique of formation of volumes of services is presented. The model is based on maintenance of constant development of manufacture
Keywords: модель формування; методика формування обсягів; manufacture volumes; formation model; technique of formation of volumes